1996
DOI: 10.1021/ie960280k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Liquid-Phase and Gas-Phase Pure Thermal Cracking of n-Hexadecane

Abstract: Thermal cracking of n-hexadecane in the mild temperature (330−375 °C) range has been investigated in liquid and gas phases. The kinetic data of liquid-phase cracking are shown to be very similar to those of gas-phase cracking. However, the pattern and distribution of the products are greatly phase dependent. In liquid-phase cracking, there is an equimolar distribution of n-alkane and 1-alkene products in the C3−C13 range at low conversion; when the conversion is increased, more alkanes than alkenes are produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 20 publications
7
62
1
Order By: Relevance
“…For n-hexadecane, the product distribution from the non-hydrous (20 bar) pyrolysis (Figures 4a and 4b) was entirely consistent with previous studies using similar conditions (Ford, 1986;Wu et al, 1996), with the lower molecular weight (˂C 14 )…”
Section: Cracked Oils and N-hexadecanesupporting
confidence: 89%
See 1 more Smart Citation
“…For n-hexadecane, the product distribution from the non-hydrous (20 bar) pyrolysis (Figures 4a and 4b) was entirely consistent with previous studies using similar conditions (Ford, 1986;Wu et al, 1996), with the lower molecular weight (˂C 14 )…”
Section: Cracked Oils and N-hexadecanesupporting
confidence: 89%
“…Ford (1986) and Wu et al (1996) concluded that the C 18 -C 31 straight and branched chain alkanes were formed by alkylation reactions between lower molecular weight (˂C 14 ) alkenes and C 16 radicals. Under normal pressure (175 bar) hydrous conditions (Figures 4a and 4b), the concentration of ˂C 14 alkenes decreased and the formation of C 18 -C 31 alkanes was completely suppressed.…”
Section: Cracked Oils and N-hexadecanementioning
confidence: 99%
“…In light hydrocarbon cracking, addition products are observed by GC upon liquid-phase cracking rather than gas-phase cracking 36) . Radical addition of polymer will yield MWDs shifted to higher MWs.…”
Section: Fragmentation Of Mid-chain Radical Andmentioning
confidence: 99%
“…Model compound studies have shown the existence of trace levels of such side reactions. 18 We have not incorporated a specific step for scission at chain branch sites (tertiary carbons). This step would be based on measurement of tertiary carbons in the polymer, possibly by nuclear magnetic resonance (NMR) characterization.…”
Section: Model Application To Hdpe Liquefactionmentioning
confidence: 99%
“…Degradation rates for light model compounds (MW Ͻ 300) show that gas phase reactions can have significant impact. 18 As time increases, the proportion of the gas phase increases as more volatiles are formed. Using b ϭ 0.85 and molecular weight of 226 (hexadecane), the rate constant was calculated to be 2.4*10 Ϫ4 s…”
Section: Data Analysis By Numerical Moment Approachmentioning
confidence: 99%